2020
DOI: 10.1103/physrevlett.124.075901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of He on the Order-Disorder Transition in Ni3Al under Irradiation

Abstract: The order-disorder transition in Ni-Al alloys under irradiation represents an interplay between various re-ordering processes and disordering due to thermal spikes generated by incident high energy particles. Typically, ordering in enabled by diffusion of thermally-generated vacancies, and can only take place at temperatures where they are mobile and in sufficiently high concentration. Here, in-situ transmission electron micrographs reveal that the presence of He-usually considered to be a deleterious immiscib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…In parallel with this experimental study, the current research group also carried out a rate-theory model and computer calculation. The theoretical work has been published separately and quantitatively explains this behaviour [38]. Calculations indicated that the V 2 He complex might play an effective role through its high stability and mobility, so helium atoms may stabilize reordering agents during irradiation at certain temperatures where the irradiation would lead to the disordering of γ' precipitates.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel with this experimental study, the current research group also carried out a rate-theory model and computer calculation. The theoretical work has been published separately and quantitatively explains this behaviour [38]. Calculations indicated that the V 2 He complex might play an effective role through its high stability and mobility, so helium atoms may stabilize reordering agents during irradiation at certain temperatures where the irradiation would lead to the disordering of γ' precipitates.…”
Section: Resultsmentioning
confidence: 99%